Investigation of sensor applications based on highly germania-doped fibers - Li, Jinhan (2018)
The dissertation is mainly to study fiber-optic sensors based on highly Germania-doped fibers. Fabrications, propagation mode analyses and experiment results of the fiber sensors with two different structures are presented. Principles of excitation of higher order propagation mode by coupling single mode fibers to multi-mode fibers are reviewed in this dissertation. Simulations are also performed to confirm the propagation modes that are transmitted in the fiber sensors. Finally, experiments are conducted to test the temperature and the strain sensitivity. The relationship between these two parameters is also analyzed. The sensor shows a fairly high-temperature sensitivity at 94pm/°C. It can be applied in a simultaneous measurement of temperature and strain with the help of the measurement matrices derived in this dissertation.